Perancangan Tata Letak Gudang Tipe Aktiva Tetap Tidak Beroperasi - Ravi Prananda Rinaldy; Yelita Anggiane Iskandar (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2022)
The Non-Operating Fixed Assets I Warehouse of Menes Baru substation used randomized storage that caused a lot of different types materials were stacked on top of each other and placed in sparsed random locations created inefficient order picking process. To solve the problem, the facility layout design using dedicated storage concept is created to minimize the order picking distance at the ATTB I Warehouse of Menes Baru substation. This research was conducted in several stages. There were (1) identifying materials and the flow patterns, including Materials Handling Equipment , (2) determining storage methods and options, and (3) analyzing activities using Activity Relationship Chart and Activity Relationship Diagram. The result shows that the recommended flow pattern material for the ATTB I Warehouse of Menes Baru substation is a U-shaped model. In addition, based on the results of the numerical scenario comparison test of order picking distances, the proposed layout using the dedicated storage concept of the ATTB I Warehouse of Menes Baru substation, could decrease the distances of order picking activity by 34% compared to the initial layout usin the randomized storage concept.